Novel Trends in the Development of Autonomation and Robotics in Metrology for Production in the Future. Issue 29 (2016) - Durakbasa, N.M.; Bauer, J.M.; Bas, G.; Kräuter, L.
Abstract: Today's manufacturing industry is going through a period of transition to the novel production technology down to micro/nanoscale of complex shapes and increasing efficiency and functionality. To meet high-level demands both from industrial and from private customers in the future, manufacturing enterprises must be high flexible and agile enough to respond quickly to product demand changes also according technological developments especially in the field of precision engineering at micro, nano and pico scale production. New levels of manufacturing precision are the key requirements to enable advanced machining processes that demands improved techniques of metrology with high flexibility, universality and high accuracy. New models for alternative configurations of future industrial organisations in general which are usually applied and especially for small and medium sized enterprises (SMEs) need to be investigated. Those new models can be developed on the basis of intelligent production technologies and integrated management systems as well as extensive use of the IT technologies, automation, robotics, parallel-processing computing and advanced engineering data exchange techniques.